A Prospective Comparative Analysis of Management of Patients of Pneumonia at Tertiary Care Centre - P. N. Kiran Kumar (Asian Journal of Medical Research, 2021)
Background: To compare management of pneumonia. Subjects and Methods : Sixty adult patients of pneumonia age ranged 18- 50 years were divided into three groups was done Group C patients were prescribed Clarithromycin 500 mg BD, group A were given azithromycin 500 mg PO then, 250 mg OD and group L were given levofloxacin 750 mg PO OD. Parameters such as temperature, cough, respiratory rate, bronchial breathing, WBC count and adverse events were recorded. Results: All groups had reduction in WBC count, temperature (degree), cough, bronchial breathing and respiratory rate recorded at day baseline, 3 and 5. However, the difference was non- significant (P> 0.05). Common adverse events were headache seen 3 in group C, 2 in group A and 4 in group L, abdominal pain 4 in group C, 5 in group A and 4 in group L and skin eruption seen 1 in group A. The difference was non- significant (P> 0.05). Conclusion: Clarithromycin, azithromycin and levofloxacin were comparable in terms of reduction in temperature, respiratory rate and cough and bronchial breathing.